(untitled) (Proceedings OPTIMAL, 2024)
Background: Breast milk is the best food for babies because it contains many substances and protective factors that are important for the growth and development of babies so that it can reduce infant morbidity and mortality. Breastfeeding that is not optimal causes hampered growth and development of the baby and is one of the factors that triggers stress in breastfeeding mothers. Many factors cause the failure of exclusive breast milk, one of which is the mother’s knowledge of breastfeeding techniques. Objective: To find out an overview of breastfeeding technique education to increase mothers’ knowledge about exclusive breast milk Method: The design of this scientific paper is descriptive using a case study approach (case study research). By sampling postpartum mothers aged 20 – 30 years in the first 24 hours after parturition. The intervention that will be carried out is to educate postpartum mothers about breastfeeding techniques to increase mothers’ knowledge in providing exclusive breast milk. Result: The nursing diagnosis of breastfeeding is ineffective a. w the mother and baby experience dissatisfaction or difficulty in the breastfeeding process p. b the baby is unable to latch onto the mother’s breast. The results after education on breastfeeding techniques and exclusive breast milk education showed that the patient’s level of knowledge regarding breastfeeding techniques and exclusive breastfeeding increased, namely: the baby’s attachment to the mother increased, the mother’s ability to position the baby correctly increased, the mother’s breast emptiness after breastfeeding increased, and the baby’s suction increased. Mother’s knowledge of exclusive breast milk greatly increased with a final score of 26 out of 30